Upgrading the old vernacular building to contemporary norms: multiple criteria approach - Šiožinytė, Eglė; Antuchevičienė, Jurgita; Kutut, Vladislavas (Journal of Civil Engineering and Management, 2014)
Sustainable development is emphasized in the process of construction or modernization of buildings at present. Old vernacular architecture does not satisfy contemporary building norms such as daylighting and/or thermal performance parameters. These parameters are important for sustainability due to their relation with energy savings. It is obvious that seeking to improve these parameters, old buildings should be upgraded. The main problem is how to reach contemporary building norms without a negative impact to architectural heritage in a process of modernisation. The aim of the research is to find the best compromise solution for effective vernacular architecture's change. The Authors suggest using multiple criteria approach that enables to evaluate possible alternative solutions in several controversial aspects and to find rational building's modernisation type. Also, suitability of combination of usual MCDM (Multiple Criteria Decision Making) methods with grey systems theory due to possibility of processing of large quantity of uncertain information is highlighted in the research. TOPSIS Grey (Technique for Order Preference by Similarity to Ideal Solution with grey numbers) and AHP (Analytic Hierarchy Process) methods are applied for the presented case study of upgrading the old vernacular building. Taking into account multiple quantitative and qualitative criteria and experts' opinion, the rational vernacular building's modernisation variant is chosen. Based on the comprehensive analysis, research conclusions and recommendations are formulated.